2008
DOI: 10.1590/s1413-78522008000500009
|View full text |Cite
|
Sign up to set email alerts
|

Bursite peritrocantérica: descrição de nova manobra semiológica para auxílio diagnóstico

Abstract: O estudo tem como objetivo testar a validade de nova manobra semiológica no diagnóstico de bursite peritrocantérica. Foram avaliados 30 pacientes, com diagnóstico clínico de bursite do grande trocanter. Todos os pacientes foram submetidos à radiografia de bacia AP e Perfil. Quando necessário, outros exames de imagem foram realizados, com a finalidade de descartar doenças associadas; os pacientes foram submetidos a duas manobras semiológicas no quadril são e afetado. TESTE 1: paciente em decúbito dorsal, o memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
(25 reference statements)
1
0
0
1
Order By: Relevance
“…The anthropometric and clinical characteristics of the population in our study were like those found in previous investigations, ( 6 ), ( 8 ), ( 13 )- ( 15 presenting female as the predominant gender and the presence of tendinopathies of the gluteus medius and minimus as the greatest cause of pain in the Greater Trochanteric Pain Syndrome (GTPS). Trochanteric bursitis was indicated in 17 hips, but this pathology was identified in association with gluteal pathology in 16 hips, like the study conducted by Bird et al, ( 13 in which trochanteric bursitis was a common and unidentified finding in the absence of gluteal pathology.…”
Section: Discussionsupporting
confidence: 81%
“…The anthropometric and clinical characteristics of the population in our study were like those found in previous investigations, ( 6 ), ( 8 ), ( 13 )- ( 15 presenting female as the predominant gender and the presence of tendinopathies of the gluteus medius and minimus as the greatest cause of pain in the Greater Trochanteric Pain Syndrome (GTPS). Trochanteric bursitis was indicated in 17 hips, but this pathology was identified in association with gluteal pathology in 16 hips, like the study conducted by Bird et al, ( 13 in which trochanteric bursitis was a common and unidentified finding in the absence of gluteal pathology.…”
Section: Discussionsupporting
confidence: 81%
“…As principais características clínicas relacionadas à SDPT, encontradas na literatura, são a dor local exacerbada por abdução forçada, fraqueza para abdução do quadril, dor em flexão, rotação interna ou externa do quadril e palpação dolorosa do trocanter maior. O diagnóstico clínico é realizado através de exames físicos e por métodos de diagnóstico por imagem, que buscam identificar alterações locais características, tais como a entesopatia do glúteo mínimo e médio, o espessamento da bursa trocantérica e a presença de edema no trato iliotibial; e ainda pela exclusão de processos patológicos ósseos degenerativos ou tumores, entre outras condições (FUJIKI et al, 2008;WILLIAMS et al, 2009). CHRISTENSEN et al, 2003);…”
Section: Lista De Figurasunclassified